2015
DOI: 10.2494/photopolymer.28.635
|View full text |Cite
|
Sign up to set email alerts
|

Sub-20 nm Microphase-Separated Structures in Hybrid Block Copolymers Consisting of Polycaprolactone and Maltoheptaose

Abstract: The present review summarizes our recent results regarding the synthesis and morphological characterization of sugar-based hybrid block copolymers (BCPs) consisting of maltoheptaose (MH) and poly( -caprolactone) (PCL). The AB-, AB 2 -, AB 3 -, ABA-, and A 2 B-type BCPs, in which the A and B blocks are MH and PCL, respectively, were synthesized by combining the living polymerization and click reaction. The in-situ small angle X-ray scattering experiments revealed the formation of ordered microphase-separated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, studies on morphology changes related to this process are very limited. 30,46,47 Otsuka et al reported order−order transition in maltoheptaose-b-poly(ε-caprolactone) diblock copolymers, and they attributed the morphology transition to the caramelization-induced volume fraction change in maltoheptaose. 30 In this study, we find that saccharide dehydration can also cause molecular changes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, studies on morphology changes related to this process are very limited. 30,46,47 Otsuka et al reported order−order transition in maltoheptaose-b-poly(ε-caprolactone) diblock copolymers, and they attributed the morphology transition to the caramelization-induced volume fraction change in maltoheptaose. 30 In this study, we find that saccharide dehydration can also cause molecular changes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, the fact that oligosaccharides can be obtained from various renewable biomass resources renders them attractive raw materials for the preparation of novel BCPs. On the basis of these advantages, we previously reported a number of oligosaccharide-containing BCP systems suitable for nanopatterning applications, including maltoheptaose- b -poly­(styrene) , and maltoheptaose- b -poly­(ε-caprolactone), to achieve microphase separation with a domain spacing of <20 nm. However, petroleum-based resources were still required for preparation of the hydrophobic polymer segments of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Since the MH/PCL BCPs promise to be fully biodegradable and biocompatible, the resulting carbohydrate-decorated nanoparticles should be of interest for applications in the biomedical fields. In addition, we have already established an efficient synthetic route toward well-defined MH/PCL BCPs involving the organocatalytic living ring-opening polymerization and click reaction, with which the precise synthesis of the linear AB-type diblock copolymers (MH- b -PCLs) and AB y -type miktoarm star polymers ( y = 2, MH- b -(PCL) 2 ; y = 3, MH- b -(PCL) 3 , respectively) had already been achieved. To gain a deeper insight into the relationship between the macromolecular architecture and nanoparticle properties, we have additionally synthesized an A 2 B 2 -type miktoarm star polymer ((MH) 2 - b -(PCL) 2 ) and two A x B-type miktoarm star polymers ( x = 2, (MH) 2 - b -PCL; x = 3, (MH) 3 - b -PCL, respectively). With these well-defined BCPs in hand, the carbohydrate-decorated nanoparticles were prepared by employing the nanoprecipitation method, and the morphology and size of the resulting nanoparticles were characterized by dynamic light scattering and microscopy measurements.…”
Section: Introductionmentioning
confidence: 99%